(untitled) (Politeja, 2017)
A World without Culture. Considerations on the Consequences of the Eugenic Revolution The intention of eugenicists has always been an attempt to repair the state of society by improving the quality of the so‑called human material. These special social reforms lead from the correction of man – conducted by means of cultivation – to the correction of the world in which he lives and develops. Eugenicists believe that if we take care of the quality of the human body, at the same time, we will take care of the quality of our social life. This article discredits this argument by showing the scarcity of the anthropology hidden in theoretical declarations of eugenicists and the naivety of the allegations about the mechanism of the development of culture. The thesis which says that a new better man creates a new and better world is shown to be as an empty dogma. In place of the standard questions about whether the world without “misfits” would be a better world the article asks the question: How would the designed luxury of total security and prosperity influence people? The answer shows that a community after the eugenic revolution is not what we call a society. The conditions of human development under eugenic treatment are not the conditions of the development of culture.